Key Considerations on CITE‐Seq for Single‐Cell Multiomics - Song, Hye‐Wong; Martin, Jody; Shi, Xiaoshan; Tyznik, Aaron J. (Proteomics (Weinheim), 2025)
ABSTRACT CITE‐Seq (Cellular Indexing of Transcriptomes and Epitopes by Sequencing) is an advanced single‐cell sequencing method to profile both gene expression and protein abundance simultaneously in individual cells using single‐cell mRNA sequencing techniques alongside antibody‐derived tags (ADTs), for protein detection. The characterization of both the transcriptome and the proteome from the same cells provides a powerful and multiomic approach for understanding the mechanisms of complex biological processes. This review focuses on the workflow of CITE‐Seq using a microwell‐based single‐cell analysis system as an example and provides key considerations for staining cells with ADTs. By highlighting critical information for CITE‐Seq library preparation, sequencing, and data analysis, this review provides a practical guide with which to perform comprehensive CITE‐Seq workflow.